Students’ expectation toward teacher’s teaching style and contribution to students’ English performance - Gita Loveta; Bambang A Loeneto; Machdalena Vianty (English Review: Journal of English Education, 2020)
Students’ expectation of their teacher’s teaching style is one of the factors that can affect academic performance. However, it is unclear how much students’ expectation affects the English academic performance of students. The objectives of this study were: (1) to find the students’ expectation on their English teacher’s teaching style, (2) to find whether the English teacher’s teaching style matches with the students’ expectation, and (3) to find the contribution of students’ expectation toward teacher’s teaching style toward their English academic performance. The study’s sample was one English teacher from each public senior high school in Sukarami District, SMA N 13, SMA N 17, and SMA N 21, along with 11th-grade students they taught. This research used descriptive quantitative design. The data were collected by questionnaire and documents as quantitative data, and interview as qualitative data. Pearson Product Moment correlation and regression were used to analyze quantitative data while transcribing was used to analyze qualitative data. The findings showed that (1) the students expected their English teacher to use Expert and Facilitator teaching style, (2) the student’s expectation is not perfectly fulfilled as the teachers prefer Expert and Formal Authority teaching style, and (3) there was no contribution of students’ expectation toward their English teacher’s teaching style to their English academic performance.